The minipig as a potential model for pedicle screw fixation: morphometry and mechanics - Robert A. Harper; Ferris M. Pfeiffer; Theodore J. Choma (Journal of Orthopaedic Surgery and Research, 2019)
Abstract Background While there are several different animal models for use in the characterization of spinal fixation, none have emerged as a definitive model for comparative studies in spinal fixation methods. The purpose of this study is to establish morphometric data of porcine vertebrae and to characterize the feasibility of pedicle screw fixation in porcine spines for potential comparative human study. Methods Four spines from 45 to 50 kg Hanford minipigs were cleaned of soft tissue and analyzed by computed tomography and dual-energy x-ray absorptiometry. Two 5 × 30-mm pedicle screws were placed in each vertebra and tested to failure using a combined moment-load protocol. Results Pedicle widths were measured from L6-T5. Widths ranged from 7.15 mm (T6) to 9.24 mm (T14). Posterior cortex to anterior cortex depth ranged from 25.9 to 32.6 mm. Mean bone mineral density was 1.0665 g/cm2 (range 1.139–1.016). Force-to-failure demonstrated mean 1171.40 N (+ 115.34). Conclusion Our baseline morphometric and compositional data demonstrate that porcine vertebrae can serve as a useful model for comparative studies due to their similar pedicle widths and bone mineral density to the human vertebra. This biomechanical data could provide a baseline comparison for future studies. This study also suggests that the minipig could be a suitable model for comparative studies due to similarities in pedicle width and bone mineral density to the human vertebrae.